ROLE OF FLOW CYTOMETRY IN THE DIAGNOSIS OF HEMATOLOGIC DISEASES - Quang Đẳng, Nguyễn; Thị Phương Anh, Đào; Thị Mỹ Linh, Nguyễn (Journal of Health and Aging, 2026)
This study aimed to describe the characteristics of common hematological disorders through immunophenotypic analysis using flow cytometry (FCM). A retrospective descriptive study was conducted on all patients aged 16 years and older who were analyzed by FCM testing at the Hematology Department, Thong Nhat Hospital from January 2023 to March 2025. Convenience sampling was applied. Data analysis was performed using Microsoft Excel 2021. A total of 104 patients were tested by flow cytometry. The median age at diagnosis was 68 years [55.8–77]. Baseline hematologic findings showed anemia (Hb 9.3 ± 2.6 g/dL) and wide variations in white blood cell (20.1 ± 42.4 K/uL) and platelet counts (197 ± 172.3 K/uL), reflecting the diversity of underlying hematologic conditions. FCM demonstrated high diagnostic value in identifying and classifying various hematologic disorders: distinguishing acute leukemia lineages (myeloid/B-lymphoid/T-lymphoid), detecting monoclonal lymphoid populations in lymphomas, and differentiating benign from malignant plasma cells in multiple myeloma. Correlation with bone marrow morphology was high, especially in diagnostically challenging cases. However, FCM could not fully replace bone marrow examination in assessing cellular morphology and tissue architecture. In conclusion, Flow cytometry is a powerful complementary tool in the diagnosis of hematologic disorders. The combination of FCM and bone marrow studies provides optimal diagnostic accuracy and supports effective patient management.